ANALISIS PERILAKU KONSUMEN: POLA PEMBELIAN KOPI SERTA PREFERENSI, KEPUASAN DAN LOYALITAS KONSUMEN KEDAI KOPI - Elly Rasmikayati; Alvi Nurin Deaniera; Dika Supyandi; Yayat Sukayat; Bobby Rachmat Saefudin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Coffee shop entrepreneurs must not only be able to sell their products and services, but also must have the ability to understand consumer tastes. This study aims to examine the behavior of coffee shop consumers from aspects of coffee buying patterns, preferences, satisfaction and customer loyalty. The study was conducted in 2 coffee shops namely Jigana Coffee Shop and Kedai Kopi Inspirasi located in Cibinong District, Bogor Regency, West Java. This study uses a quantitative research design conducted by survey methods on 27 consumers of Jigana Coffee Shop and 45 consumers of Kedai Kopi Inspirasi obtained through systematic sampling techniques through the calculation of the Cochran formula. Data analyzed using frequency distribution tables. The results showed that the pattern of coffee purchases by consumers in Jigana Coffee Shop and Coffee Shop Inspiration mostly with the reason simply wanted to try and want to get a comfortable atmosphere by drinking coffee in a coffee shop and chatting with friends or spouse around 17:00 to 21:00. Discounts and "buy one get one" promotions greatly affect consumer interest in visiting coffee shops. While in terms of consumer preferences, the most preferred types of drinks are Espresso based and Manual Brew. As for the types of drinks the most preferred by consumers are french fries and toast. Then regarding satisfaction and loyalty, most consumers were satisfied after a visit to the coffee shop and were interested in making a repeat visit.